Implementation Strategy Branding New Product: Promotion, Quality Product and Influencer - Muliyati Muliyati; Dewi Endah Fajariani; Nurhayati Nurhayati; Rahmat Jaya; Ryan Firdiansyah Suryawan (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2023)
The purpose of this article is to better understand the dynamics and interaction between the three elements, companies can optimize their branding strategies and achieve success in marketing their new products. The research methods in this article use techniques by describing a result, with the Analysis collecting the necessary data from additional sources, which are then analysis and explained properly, For the purpose of conducting research, additional information collected books, research papers, articles, lecture notes, the internet, and other information sources are used to collect more data. The results of implementing branding strategies for new products, promotions, quality products, and influencer influence have a significant role. Based on research and understanding of marketing concepts, here are the conclusions that can be drawn: Promotion is key in introducing new products to consumers. Through effective promotional campaigns, companies can increase brand and product awareness among consumers. It is important to design an attractive promotional campaign and choose the right communication channels to reach the target audience.